Redrawing Power: #YoSoy132 and Overflowing Insurgencies - Favela, Mariana (Social justice, 2015)
The author shares her reflections about #YoSoy132 which is a mass insurgency that emerged during the presidential campaign in Mexico in 2012. Topics discussed include presidential candidate Enrique Peña Nieto's restriction of the number of college students who can attend his campaign, students' launch of a video in social networks with the hashtag #YoSoy132 to call for a dialogue about the democratization of the country's politics, and several protests held between May and December 2012.